PENGARUH TERAPI RELAKSASI SPIRITUAL TERHADAP TINGKAT STRES PASIEN GAGAL GINJAL KRONIS YANG MENJALANI HEMODIALISIS - Ningsih, Etik Dwi; Mukarromah, indah (STIKes Maharani Malang, 2018)
Introduction: The stress experienced by patients with chronic renal failure who undergo hemodialysis may aggravate a person's condition such as disobedience to diet and fluid modification and treatment if not treated properly. Spiritual relaxation was a method of lowered stress, one's effort to achieve relaxed state through spiritual religious beliefs. The purpose of the study, looking at the effect of spiritual relaxation on stress levels in patients with chronic renal failure who underwent hemodialysis. Method: Pre experimental method one group pre and posttest design with 10 respondents sample through technique of proposive sampling. The independent variable was spiritual relaxation and the dependent variable of stress level. The stress level was measured by HSS Instrument (hemodialysis stress scale) and spiritual relaxation used Standard Operating Procedures. Spiritual relaxation performed once per week for 1 month. it analyzed by Wilcoxon test with α = 0,05. The result was a significant difference between stress level before and after intervention p = 0,004 (p<α) it means there was influenced. Result and analysis: Spiritual relaxation balanced the sympathetic and parasympathetic nerves when relaxed conditions were effective in reduced stress and maintained the psychological health of patients with chronic renal failure. Discussion: Spiritual relaxation can be used as an alternative to nursing actions and examine hormonal changes in stress reduction